Isolating and Identifying Root-Fungi (Mycorrhiza) Symbiotic with Tomato in the Syrian Coast - Khrieba, Mohammad Imad; Ghazal, Ibtissam; Azmeh, Mohammad Fawaz; Choumane, Wafaa; Zangeneh, Sima (Latakia University Journal -Biological Sciences Series, 2013)
The objective of this study is to identify some species of mycorrhizal fungi coexisting with tomato roots in the Syrian coast. Samples were collected from five sites in two different regions: Lattakia (sites: Siano and ALbrjan) and Tartous (sites: Majdalon Elbahr, Mayaar Shaker and Hrysoon). Four samples of soil and tomato roots were collected from each site and mixed together to form a composite sample/site. Morphological characterization of isolated fungi was based on universally adopted taxonomic keys, and on the classification keys approved by the Plant Protection Research Institute of Iran. Six types of mycorrhizal fungi belonging to 5 species were identified in the different sites. Paraglomus laccaltum was present in one site (Siano), Septoglomus constrictum was isolated from 2 sites (Mayaar Shaker and Majdalon Elbahr), Claroideoglomus etunicatum was also isolated from 2 sites (Mayaar Shaker and Siano), Simiglomus hoi was present in 3 sites (Siano, Majdalon Elbahr and ALbrjan), Glomus fasciculatum was present in four sites (Siano, Mayaar Shaker, ALbrjan and Hrysoon) and Glomus clarum was present in four sites (Hrysoon, Siano, Mayaar Shaker, and Majdalon Elbahr).